CORRECTIONAL WORK IN THE DEVELOPMENT OF SPEECH IN PRESCHOOL-AGED CHILDREN WITH MUSCULOSKELETAL CHALLENGES - Soliyev Ilhomjon Sobirovich; Isodullayeva Iqboloy Sodiqjonovna (American Journals Publishing, 2024)
This article talks about the types of children's cerebral palsy, their causes, and speech exercises used to eliminate speech defects in them.
Keywords: Cerebral palsy, etiology, dysarthria, complex exercises.